Aeroacoustic Source Potential Based on Poisson’s Equation - Schoder, Stefan; Mohamadi Bagheri, Eman; Spieser, Étienne (AIAA Journal, 2024)
Poisson’s equation is an important equation to postprocess the aerodynamic fields into linearized momentum modes and was recently found to be important for the computation of an isotropic pressure-like source for scalar aeroacoustic wave models, like the aeroacoustic wave equation based on Pierce’s operator (AWE-PO). Mathe-matically viable boundary conditions of the Poisson equation, which computes the AWE-PO source, are investigated. For the different source fields, the wave propagation is computed using the AWE-PO, and the details of the sound prediction results are compared to a reference direct numerical simulation of a mixing layer. The different boundary conditions of the Poisson equation were found to have a minor influence on the overall sound prediction characteristics of the AWE-PO equation. The AWE-PO is reformulated into a simplified version of the Phillips’s equation, which mitigates the intermediate step of computing an isotropic source potential. By doing so, a previously obtained interference radiation valley in the radiated acoustic intensity of the AWE-PO results is attributed to a missing shear-noise source term.
CRIS-Team Scopus Importer:2024-11-15